Some aspects of the clinical picture and dynamics of the postwithdrawal period in opium addiction patients - A. A. Abetova; M. T. Meldekhanova (Бюллетень сибирской медицины)
The psychopathological pattern of the postwithdrawal state in opium addiction patients is discussed. The pathological addiction to the drug in dependence of premorbid personality characteristics and the inverse dynamics are analyzed.